Wealth effects on household final consumption: Stock and housing market channels - Yener Coskun; Burak Sencer Atasoy; Giacomo Morri; Esra Alp (International Journal of Financial Studies, 2018)
The study primarily explores the linkage between wealth effects, arising from stock and housing market channels, and household final consumption for 11 advanced countries over the period from 1970 Q1 to 2015 Q4. As a modelling strategy, we employ regression analysis through the common correlated effects mean group (CCEMG) estimator, as well as Durbin-Hausman cointegration and Dumitrescu and Hurlin (2012) causality tests. The study provides various pieces of evidence through whole-panel and country-level analyses. In this respect, we find that consumption is mostly explained by income and housing wealth is positively and significantly correlated with consumption. As counter-intuitive evidence, we detect a negative linkage between consumption and stock wealth. The evidence also suggests a long-run cointegration relationship among consumption, income, interest rates, housing wealth, and stock wealth. Moreover, we find bidirectional causality between consumption and income, stock wealth, housing wealth, and interest rates. Overall, the evidence implies that housing wealth, rather than stock wealth, is the primary source of consumption growth in advanced countries.
Keywords: D12; E21; R31; 330; consumption; housing wealth; stock wealth; asset transmission; CCEMG